Honey B. & T-Bones. - Honey B. & T-Bones; EMI Finland (Helsinki : EMI Finland, 1986)
4 kappaletta.
Surfin' U.F.O. ; Queen Bee ; Shake your moneymaker ; While the cat's away.
Honey B. and the T-Bones (yhtye).
Keywords: Honey B. & T-Bones -- EP:t.